2001
DOI: 10.1590/s0074-02762001000800011
|View full text |Cite
|
Sign up to set email alerts
|

Wing geometry as a tool for studying the Lutzomyia longipalpis (Diptera: Psychodidae) complex

Abstract: Toro Toro (T) and Yungas (Y) have been described as genetically well differentiated populations of the Lutzomyia longipalpis (Lutz & Neiva, 1912)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 19 publications
0
12
0
6
Order By: Relevance
“…geniculatus Mangabeira, 1941 that originated in two different geographical areas described that the analysis of canonical variates was able to separate the species when CV1 was observed and separate the geographical regions when CV2 was observed. In contrast, a study done by De la Riva et al (2001) with populations of species of Lutzomyia longipalpis Lutz & Neiva, 1912 using 5 anatomical landmarks on the wings showed an inability to separate populations from diverse geographical regions while, at the same time, managing to group these population into two groups, one with specimens of the most heterogeneous areas and the other with specimens from the more homogeneous areas. Prudhomme et al (2012) compared the wings of Phlebotomus papatasi in different regions of Morocco (North and South) using 16 anatomical landmarks on the wings.…”
Section: Discussionmentioning
confidence: 85%
“…geniculatus Mangabeira, 1941 that originated in two different geographical areas described that the analysis of canonical variates was able to separate the species when CV1 was observed and separate the geographical regions when CV2 was observed. In contrast, a study done by De la Riva et al (2001) with populations of species of Lutzomyia longipalpis Lutz & Neiva, 1912 using 5 anatomical landmarks on the wings showed an inability to separate populations from diverse geographical regions while, at the same time, managing to group these population into two groups, one with specimens of the most heterogeneous areas and the other with specimens from the more homogeneous areas. Prudhomme et al (2012) compared the wings of Phlebotomus papatasi in different regions of Morocco (North and South) using 16 anatomical landmarks on the wings.…”
Section: Discussionmentioning
confidence: 85%
“…Schrö derÕs study revealed a classiÞcation rate of 98% and a correct reassignment rate of 54%. Recently, the method of geometric morphometry was successfully applied to studies of ßies and beetles (De la Riva et al 2001, Garnier et al 2005. Garnier et al (2005) used the method to clariÞed the phylogeographic history of a ground beetle (differentiation within two different glacial refuges and recolonization routes).…”
Section: Discussionmentioning
confidence: 99%
“…The authors used the shape of the aedeagus and the pronotum for their morphometric analyses. Del la Riva et al (2001) used wing morphology to differentiate ßy populations in South America and reclaimed the morphometric analyses as a successful and less expensive tool in comparison with molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…After superimposition, the landmark configurations differ only in shape and can be analysed by multivariate statistical methods (Rohlf and Marcus 1993;Zelditch et al 2004). Wing shape variation of insects at different taxonomic levels have been studied using GM (De La Riva et al 2001;Pretorius and Scholtz 2001;Monteiro et al 2002;Houle et al 2003;Schachter-Broide et al 2004;Pretorius 2005;Aytekin et al 2007;Sadeghi et al 2009). In addition, wing shape variation based on GM has been used to discriminate and identify honeybee subspecies (Francoy et al 2008;Tofilski 2008), the heritability of wing shape (Monteiro et al 2002) and the influence of hybridization on fluctuating asymetry (Schneider et al 2003).…”
Section: Introductionmentioning
confidence: 99%